THE SIGNIFICANCE OF THE GRI (GLOBAL REPORTING INITIATIVE) STANDARD IN REPORTING OF ENVIRONMENTAL INFORMATION. THE ANALYSIS OF POLISH BANKING SECTOR IN THE FACE OF REGULATORY CHANGES - Zabawa, Justyna (Copernican Journal of Finance & Accounting, 2018)
One of the most notable effects generated in response to the recent spate of regulatory changes in the banking sector is the mounting interest in those elements of sectoral policy that focus on disclosure of non-financial information – a trend observed not only in Poland, but also in the EU financial sector as a whole. This phenomenon may also be related to the 2014/95/UE Directive. The main objective of this paper is to verify the thesis that the GRI standard can be seen as the dominant standard for reporting non-financial (including environmental) information in Polish banking organisations under the pending legal standards and regulations. In addition, the author intends to fill the apparent gap in professional literature, as the subject of reporting non-financial information (in particular – environmental information) in the banking sector seems under-represented in modern research. The paper examines 20 largest banks in Poland. The basic method used in the process of writing was a critical analysis of financial and non-financial-reports of analyzed commercial banks, and literature concerning non financial reporting in banking sector. The structure of the article consists of six parts: introduction; the research methodology and the course of the research process; reporting of the social and environmental responsibility – literature review; GRI as a main standard in reporting of non-financial information; the situation of Polish banking sector in 2016, main findings and results and the last part: conclusions.